Prevalence of heart failure and coronary artery disease in older adults experiencing homelessness: A systematic review and meta-analysis protocol with a consultative exercise - Kristina M. Kokorelias; Yu Qing Huang; Maurita T. Harris; Peter M. Hoang (PLoS ONE, 2026)
Background Heart failure (HF) is a major global public health challenge and a leading cause of morbidity and mortality, particularly among older adults. The rising prevalence of HF is driven by aging populations and the increasing burden of chronic conditions such as hypertension, diabetes, and obesity. In Canada alone, over 750,000 individuals live with HF, with over 100,000 new cases diagnosed annually. Despite advancements in pharmacological and device-based treatments, HF remains a primary cause of hospital admissions, with readmission rates exceeding 20% within 30 days. The associated healthcare costs are projected to reach $2.8 billion annually by 2030. Objective Older adults experiencing homelessness represent a particularly vulnerable population at risk for HF. Homelessness is associated with increased exposure to cardiovascular risk factors, including inadequate access to preventive healthcare, high rates of comorbid conditions, and environmental stressors. Evidence suggests that individuals experiencing homelessness have a significantly higher incidence and earlier onset of HF compared to the general population, yet this intersection remains underexplored in the literature. This paper outlines the protocol for a systematic review and meta-analysis that aims to address this gap by synthesizing the prevalence, incidence, and mortality of HF among older adults who have experienced homelessness. Methods This systematic review will follow the PRISMA and MOOSE guidelines and has been registered on the Open Science Framework. We will include studies examining the prevalence, incidence, or mortality of HF among older adults (aged 50 and above) with a history of homelessness. The decision to lower the age threshold to 50 reflects the accelerated aging process observed in this population, who often experience age-related conditions at a younger chronological age. Eligible study designs include cross-sectional, cohort, and case-control studies. Quantitative data from peer-reviewed publications and grey literature will be included, with no language or date restrictions. A comprehensive search strategy will be applied across major electronic databases, including Medline, Embase, Cochrane Library, and ISI Web of Science. We will also perform grey literature searches through Google Scholar and governmental websites. Backward citation tracking will be conducted to identify additional relevant studies. Study selection will involve independent screening by three reviewers, with disagreements resolved by consensus. Data extraction will include study characteristics, participant demographics, and HF-related outcomes. Risk of bias will be assessed using the Joanna Briggs Institute Checklist for Prevalence Studies and the ROBINS-E tool for non-randomized studies. Results The review will estimate pooled prevalence, incidence, and mortality rates of HF in older adults experiencing homelessness. Where possible, we will conduct subgroup analyses based on age, sex, and comorbidities. Meta-regression and sensitivity analyses will be performed to assess the robustness of the findings. Conclusion This systematic review and meta-analysis will provide the first comprehensive synthesis of HF epidemiology in older adults experiencing homelessness. By identifying disparities in cardiovascular health outcomes, this study aims to inform public health policies, healthcare delivery, and future research to improve cardiovascular care for this marginalized population.